A framework for accelerating neuromorphic-vision algorithms on FPGAs - DeBole, M.; Maashri, A. A.; Cotter, M.; Yu, C.-L; Chakrabarti, C.; Narayanan, V. (2011 IEEE/ACM International Conference on Computer-Aided Design (ICCAD), 2011)
Implementations of neuromorphic algorithms are traditionally implemented on platforms which consume significant power, falling short of their biologically underpinnings. Recent improvements in FPGA technology have led to FPGAs becoming a platform in which these rapidly evolving algorithms can be implemented. Unfortunately, implementing designs on FPGAs still prove challenging for nonexperts, limiting their use in the neuroscience domain. In this paper, a FPGA framework is presented which enables neuroscientists to compose multi-FPGA systems for a cortical object classification model. This is demonstrated by mapping this algorithm onto two distinct platforms providing speedups of up to ~28X over a reference CPU implementation.